التحري عن بعض الأمراض الفيروسية على محصول الفليفلة في المنطقتين الوسطى والساحلية من سورية - إسماعيل, عماد; القاعي, باسل; يوسف, ريم (Latakia University Journal -Biological Sciences Series, 2018)
هدف البحث إلى التحري عن فيروسات موزاييك الخيار وموزاييك الفصة وموزاييك التبغ وواي البطاطا واكس البطاطا في حقول الفليفلة في المنطقتين الوسطى والساحلية من سورية خلال صيف وخريف 2006. وبلغ عدد العينات الكلي /3277/ عينة, منها /2560/ عينة من المنطقة الوسطى (29 حقلاً في حماة و6 حقول في حمص) و/717/ عينة من المنطقة الساحلية (8 حقول في اللاذقية و17 حقلاً في طرطوس). أظهرت نتائج اختبار البصمة النسيجية المناعية (TPIA) على العينات المُختبرة إصابة محصول الفليفلة في مناطق الدراسة بجميع الفيروسات المدروسة وبنسب مختلفة, وكان فيروس موزاييك الخيار الأكثر انتشاراً في عينات الفليفلة المُختبرة (50.7%) يليه على التوالي فيروس موزاييك الفصة (22.2%), فيروس موزاييك التبغ (17.8%), فيروس واي البطاطا (14.4%), فيروس إكس البطاطا (10.8%). وكانت فيروسات موزاييك الخيار وموزاييك التبغ وواي البطاطا أكثر انتشاراً في عينات المنطقة الساحلية (34.4%, 23.7%, 18.3% على التوالي), في حين كان فيروسي موزاييك الخيار وموزاييك الفصة أكثر انتشاراً في عينات المنطقة الوسطى (55.2%, 24.9% على التوالي). ويُعد هذا البحث أول تسجيل لفيروسات الفليفلة في سورية. The objective of this study was to survey Cucumber mosaic cucumovirus (CMV), Tobacco mosaic tobamovirus (TMV), Potato X potexvirus (PVX), Potato Y potyvirus (PVY) and Alfalfa mosaic alfamovirus (AMV) in pepper fields of central and costal regions of Syria during Summer and Fall seasons 2006. In total /3277/ samples have been collected: /2560/ samples from central region fields (Hamah/29 fields and Homs/6 fields) and /717/ samples from costal region fields (Lattakia/8 fields and Tartous/17 fields). Results of tissue print immunoassay (TPIA) of tested samples showed the infection of pepper crop in all surveyed areas with the above viruses in various ratios. CMV dominated tested samples (50.7%) followed by AMV (22.2%), TMV (17.8%), PVY (14.4%) and PVX (10.8%) respectively. CMV, TMV and PVY were dominant in pepper samples collected from costal region (34.4%, 23.7% and 18.3% respectively), while CMV and AMV dominated pepper samples collected from central region (55.2% and 24.9% respectively). This paper is the first record of pepper viruses in Syria.